2018
DOI: 10.33899/rden.2018.160842
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Peri Implant Osteal Changes by Radiographic Evaluation Using Standard Orthopantomograph and Periapical View a Retrospective Study

Abstract: ‫الخالصة‬ ‫االهداف‬ ‫الؼظو‬ ‫األًسجت‬ ‫فٍ‬ ‫الخغُشاث‬ ‫ػلً‬ ‫الزسوَت‬ ‫واألشؼت‬ ‫الباًىساها‬ ‫أشؼت‬ ‫اسخخذام‬ ‫حقُُن‬ ‫الً‬ ‫البحث‬ ‫َهذف‬ : ‫ةلت‬ ‫الحا‬ ‫األسةٌاى‬ ‫صسػةت‬ ‫وةىز‬ ‫ُةت‬ ‫الضسػةاث‬ ‫بٌجةاا‬ ‫للخىقةغ‬ ‫هؼُاسا‬ ‫واػخباسها‬ ‫أشهش‬ ‫بأسبؼت‬ ‫وبؼذها‬ ‫الضسػت‬ ‫وضغ‬ ‫ػٌذ‬ ‫اللمو‬ ‫طرااقوا‬ ‫المواا‬ ‫ةا‬ ‫هشَ‬ ‫ػاةش‬ ‫حسةؼت‬ ‫ت‬ ‫هاةاس‬ ‫حةن‬ : ‫ال‬ ‫واشةز‬ ‫لخحلُة‬ ‫الةذَوا‬ ‫كهةاص‬ ‫وباسةخخذام‬ ‫لسسةٌاى‬ ‫رسوَةت‬ ‫وأشةؼت‬ ‫باًىساهةا‬ ‫أشةؼت‬ ‫اشةز‬ ‫وحةن‬ ‫صسػةت‬ ‫وػاةشَي‬ ‫أسبؼةت‬ ‫وباسخخذام‬ ‫للؼظ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…They concluded that orthopantomograph is an average radiographic tool as it does not allow an operator to quantify different bone levels at different sections. [ 14 ] However, with the latest three-dimensional radiographies like CBCT, these issues have been largely resolved. In our study, the authors studied precise crestal bone losses at different time intervals by CBCT.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that orthopantomograph is an average radiographic tool as it does not allow an operator to quantify different bone levels at different sections. [ 14 ] However, with the latest three-dimensional radiographies like CBCT, these issues have been largely resolved. In our study, the authors studied precise crestal bone losses at different time intervals by CBCT.…”
Section: Discussionmentioning
confidence: 99%